Kinerja Perusahaan Umum Daerah Air Minum Tirta Sago dalam Penyediaan Air Bersih di Kota Payakumbuh - Risa Putri; Khairul Amri (Eksekusi : Jurnal Ilmu Hukum dan Administrasi Negara, 2024)
The performance of the Tirta Sago Regional Drinking Water Company in providing clean water in Payakumbuh City is still not optimal. This Research aims to determine the performance of the regional pub;ic company for drinking water tirta sago and what inhibiting factors influence its performance both technically and in administrative services. This research uses agus dwiyanto”s (2021) permormance theory wich provides 5 assessment indicators, namely : Productivity, service quality, responsiveness, responsibility, and accountability. The method used in this research is a qualitative approach with data colelection techniques in the form of observation and interviews. The results of this distribution targets is decreasing accompanied by the level of water loss which is still at 35 %, in terms of quality of service there are still employes who provide services that do not comply with regulation, then in terms of responsiveness indicators there is a new innovation in the form of Smart Water Company but the level of urgency of costumer complaints regarding water distribution that does not meet costumer needs there is no respons from company, then based on responsibility indicators there are still errors is manually checking water meters which have an impact on costumer water billing so that the administration procces not going well, then in terms of accountability it is still not optimal because the regional public company for drinking water tirta sago received a warning from the DPRD through mayor to the evaluate the profits obtained. The problems that occur are caused by factors, namely infrasturctur that is not yet adequate and utilized optimally, poor coordination between employes and management, the system for checking water meters is still done manually, and revruitment regulation that are not strict in preventing fraud.